Online Service Acceptance Model of Population and Civil Registration Agency in Indonesia using Technology Acceptance Model - Wulan Safutri; Dini Turipanam Alamanda; Abdullah Ramdhani; Nadhira Fauziyyah (Publikasi Indonesia, 2024)
The application of online services at the Population and Civil Registry Service (Disdukcapil) in Indonesia is important in increasing the efficiency and quality of public services. However, the success of reveiving online services is still a major concern for the government and public service managers. Therefore, this study aims to analyze the online service acceptance model at Disdukcapil in Indonesia using the Technology Acceptance Model (TAM). The data collection method was carried out through a survey of potential users of online services and using Partial Least Squares – Structural Equation Model (PLS – SEM) to analyze the data. The results showed that perceived ease of use, perceived usefulness, attitudes towards system, behavioural intention and the actual system usage which are the dimensions of the Technology Acceptance Model have a positive effect on acceptance of online services at Disdukcapil in Indonesia. The findings can be used as a guide for policy makers and public service managers to increase acceptance and adoption of online services in the government sector. In addition, this research is expected to provide a strong foundation in improving and improving public services effectively using technology.